2001
DOI: 10.1002/imhj.1003
|View full text |Cite
|
Sign up to set email alerts
|

Postneonatal mental and motor development of infants exposed in utero to opioid drugs

Abstract: We compared the mental and motor development of 33 infants from innercity, African American families whose mothers used opioid drugs during pregnancy with that of 45 infants from demographically comparable families where the mothers were not users of opioids. We found that during the first 2 years of life, the children exposed to opioid drugs showed poorer functioning on Bayley Scales mental and psychomotor development indices as well as on Infant Behavior Record ratings of mental and motor functioning. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
77
2
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 43 publications
2
77
2
2
Order By: Relevance
“…The significant effect sizes were in the range of approximately 0.5 to 0.9 standard deviations. The combination of cognitive functions within the normal range but significantly worse than a non-exposed group is in accordance with previous studies of young children with prenatal opioid or poly-drug exposure (Bauman & Levine, 1986;Bunikowski et al, 1998;Hans & Jeremy, 2001;Hunt et al, 2008;Johnson et al, 1984;Logan et al, 2011;van Baar & de Graaff, 1994;Wilson, 1989;Wilson et al, 1979) and youths with such prenatal exposure (Davis & Templer, 1988;Ornoy et al, 2010).…”
Section: Cognitive Scores and Group Differencessupporting
confidence: 91%
See 3 more Smart Citations
“…The significant effect sizes were in the range of approximately 0.5 to 0.9 standard deviations. The combination of cognitive functions within the normal range but significantly worse than a non-exposed group is in accordance with previous studies of young children with prenatal opioid or poly-drug exposure (Bauman & Levine, 1986;Bunikowski et al, 1998;Hans & Jeremy, 2001;Hunt et al, 2008;Johnson et al, 1984;Logan et al, 2011;van Baar & de Graaff, 1994;Wilson, 1989;Wilson et al, 1979) and youths with such prenatal exposure (Davis & Templer, 1988;Ornoy et al, 2010).…”
Section: Cognitive Scores and Group Differencessupporting
confidence: 91%
“…The few studies of young children indicate the likelihood of problems within fields related to executive control and attention (Hans, 1996;Hickey, Suess, Newlin, Spurgeon, & Porges, 1995;Melinder, Konijnenberg, & Sarfi, 2013;Ornoy, Segal, Bar-Hamburger, & Greenbaum, 2001;Slinning, 2004;Wahlsten & Sarman, 2013) and behavior regulation (de Cubas & Field, 1993;Hans, 1996;Sowder & Burt, 1980). Fine motor abilities, which are often related to executive control (Rigoli, Piek, Kane, & Oosterlaan, 2012), have also been found to be worse among young children born to mothers with opioid and poly-drug use during pregnancy than among other children (Bunikowski et al, 1998;Davis & Templer, 1988;Hans & Jeremy, 2001;Logan et al, 2011). Some studies find that motor abilities are the most affected functional area (Bernstein, Jeremy, Hans, & Marcus, 1984;Hans, 1989;Wahlsten & Sarman, 2013), whereas other studies have not found significant group differences in motor abilities (van Baar, 1990).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Suess et al, 1997;Moe and Slinning, 2002;Moe, 2002;Slinning, 2004). This relationship can partly be explained by environmental correlates of maternal substance-abuse, including higher level of social risk (Hans and Jeremy, 2001), such as effects of poverty, stress, maternal psychopathology, disruptions in maternal care, and poorer interaction with the primary caregiver. However, developmental difficulties of children born to substance-abusing mothers likely also have potent biological foundations.…”
Section: Introductionmentioning
confidence: 99%